Issue Information – Cover. (23rd September 2016) - Unknown
Abstract : Confocal immunofluorescence image of retinal microglial cells from a C57BL/6J mouse undergoing non‐ocular conditions: immunosuppression (by cyclophosphamide) and peripheral inflammation (sublethal colitis chemically‐induced with dextran sulphate sodium salt), both administered systemically. Microglial cells (Iba1 positive cells, in green) present an activated state, with an elongated soma and immunoreactivity against MHCIIRT1B antibody (red fluorescence, coexpression is seen in yellow). Cells are spread through different retinal layers (outer plexiform, inner nuclear, inner plexiform and ganglion cell layers). Non‐specific immunoreactivity of the secondary antibody (in red) to blood vessels is also observed. Microbiol Immunol : 60:617–625.Article link here .